Perencanaan Armada, Pengendalian Persediaan, Dan Peningkatan Layanan Distribusi Air Minum Kemasan - Firda Annisa Septiana; Okin Ringan Purba; Dian Anom Baskoro (Jurnal Manajemen Bisnis Transportasi dan Logistik, 2020)
The purpose of this research is to do empirical test to know how much the influence of transportation fleet planning is and controlling goods inventory of the improvement of goods distribution services. This research used a case study of distribution division or finished goods warehouse of a drinking water company. The data collection was carried out by perception survey of 48 warehouse employees as subject research on variable study. Multiple regression was used to analyse the data. The result of this research shows that regression equation Y=11,584 + 0,387X1 + 0,368X2. The fleet planning and inventory control have a significant influence and strong relationship to the improvement of distribution services